Documenting Cooperative Extension’s Family Resource Management Impacts: Insights and Outcomes from a National Effort - Suzanne Bartholomae; Elizabeth Kiss; Maria Pippidis (Journal of Human Sciences and Extension)
Family Resource Management (FRM) professionals of the Cooperative Extension System contribute to the financial security and well-being of individuals and families and are committed to contributing to financial literacy education scholarship and better positioning Cooperative Extension within the field of financial and consumer education. This paper presents a summary of a multi-year initiative by a team of FRM Extension professionals who build the case for creating a reporting system to document FRM impacts nationally. Initiative activities are summarized and include reviewing existing reporting systems, garnering input from FRM Extension professionals about the delivery and evaluation of FRM programs, identifying barriers and solutions to establishing a common reporting system, developing tools, a logic model, and an inventory of common indicators, concept testing a data collection model, and aggregating multi-state data on FRM outputs and incomes. The paper highlights the processes of the initiative, lessons learned, and the next steps. A reporting system that allows FRM program impacts to be shared with a broader audience, whether stakeholders, funders, or the research community, is timely and important for the viability of the FRM program area at a time when FRM content is being subsumed into or replaced by other programs.